Computer Evaluation of Asperity Topology of Rock Joints - Ficker, Tomáš; Martišek, Dalibor (Elsevier, 2015)
Grounds beneath large civil engineering structures (bridges, dams, tunnels) that are established in the terrain of rock discontinuities represent a risk of mechanical failure. The surface topology of joint surfaces strongly influences shear strength of these discontinuities. It is the asperities that mainly determine the surface topologies and the asperities are characterized by the so-called joint roughness coefficients. In geotechnical practice the joint roughness coefficients are often evaluated visually using ten standard two-dimensional profiles. The visual assessment is rather a subjective procedure but it may be replaced by a computer procedure. The present paper deals with a computerized assessment of joint roughness coefficients. For this purpose the Fourier formalism is employed and works as an expert system recognizing surface topologies.

Grounds beneath large civil engineering structures (bridges, dams, tunnels) that are established in the terrain of rock discontinuities represent a risk of mechanical failure. The surface topology of joint surfaces strongly influences shear strength of these discontinuities. It is the asperities that mainly determine the surface topologies and the asperities are characterized by the so-called joint roughness coefficients. In geotechnical practice the joint roughness coefficients are often evaluated visually using ten standard two-dimensional profiles. The visual assessment is rather a subjective procedure but it may be replaced by a computer procedure. The present paper deals with a computerized assessment of joint roughness coefficients. For this purpose the Fourier formalism is employed and works as an expert system recognizing surface topologies.
Computer Evaluation of Asperity Topology of Rock Joints
Keywords: Rock joints; joint roughness coefficients; Fourier’s formalism; indicators of surface topology.; Rock joints; joint roughness coefficients; Fourier’s formalism; indicators of surface topology.